The author and his shadow. On the work The Thersites´s Lessons - Cuesta Fernández, Raimundo; Hernández Sánchez, Gustavo (Historia y Memoria de la Educación, 2018)
By combining historiographical reflection with an autobiographical narrative, this piece of research is made up of three separate parts. First, an essay by Raimundo Cuesta, where he explains his intellectual autobiography as applied to his last book, Thersites’s Lessons. Secondly, an interview with Raimundo Cuesta, conducted by the young historian Gustavo Hernández Sánchez. And lastly, Hernández Sánchez’s review and synthesis of Cuesta’s recent book, which is then included in the corresponding section of the journal, as a pretext for describing his personal and intellectual relationship with the author